Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve for this Variable. 5z - 2 = 2 (3z - 4)

Sagot :

[tex]5z-2=2(3z-4) \\ \\ 5z-2=6z-8 \\ \\ 5z=6z-6 \\ \\ -z=-6 \\ \\ z=6[/tex]

Distribute the 2 with the (3z-4) after distributing the 2, your answer would look like this: 5z-2=6z-8

then you would add 2 to both sides and your equation would look like this:          5z=6z-6

next you would subtract the 6z to both sides and your equation would look like this:  -z=6

I think that is your answer sorry I tried.